The Concept of Polyphony in Moroccan Legal Discourse: From the Legislative Text to the Judicial Ruling (Linguist, 2026)
This research paper seeks to highlight the significant importance that the concept of polyphony has acquired in the field of law. By dedicating greater attention to this notion, we emphasize the role of polyphonic structures within legal discourse in general, and more specifically within legislative and judicial discourse. Indeed, such multiplicity of voices often confuses non-specialists, and we argue that it constitutes a strong barrier for those unfamiliar with the intricacies of legal discourse in its entirety. Law, in addition to being a set of rules that regulate individual behavior within society, is also a coherent corpus whose themes are harmonized and interconnected, flowing seamlessly from one to another without unnecessary complexity. This coherence and consistency are subject to a precise scientific and logical order, which manifests itself in the articulation of its purposes through its texts and provisions.
Keywords: Legal Discourse; Polyphony; Legal Rule; Dialogue; Lawsuit; Court